IMPLEMENTASI CERTAINTY FACTOR DALAM DIAGNOSA PENYAKIT KEJIWAAN - Marhalim Marhalim; Andilala Andilala; Toto Dwi Putra; Nopa Adiansa (JTIS: Journal of Technopreneurship and Information System, 2021)
ABSTRACT - Along with the development of technology, a technology system that is able to adopt the process and way of thinking of humans is also developed, namely Artificial Intelligence technology. An expert system is one part of artificial intelligence that contains certain knowledge so that everyone can use it to solve various specific problems, in this case, mental health problems. Most people who experience psychiatric symptoms are still reluctant to go to a doctor or a psychiatrist because of the limited places for consultation. With these limitations the role of the expert system is very important in solving a problem. The problem is a mental illness. The purpose of building this expert system is to help people who suffer from mental illness consult online without having to come directly to a doctor or psychiatrist. Making Expert System is presented using the Certainty Factor method. using some software that is used for making applications from start to finish, for example Xampp, Mysql, Adobe Dreamweaver and other supporting software.Keywords : Artifical Intelligence, Expert System, Psychiatric Diseases, MySql, AdobeÂ  Dreamweaver.